Liquidity and congestion - Gara M. Afonso (Federal Reserve Bank of New York, 2008)
This paper studies the relationship between the arrival of potential investors and market liquidity in a search-based model of asset trading. The entry of investors into a specific market causes two contradictory effects. First, it reduces trading costs, which then attracts new investors (the thick market externality effect). But second, as investors concentrate on one side of the market, the market becomes 'congested,' decreasing the returns to participating in this market and discouraging new investors from entering (what we call the congestion effect). The equilibrium level of market liquidity depends on which of the two effects dominates. When congestion is the leading effect, some interesting results arise. In particular, we find that diminishing trading costs in our market can impair liquidity and reduce welfare.
Keywords: G12; D40; 330; Liquidity; search; congestion; asset pricing